Oxygen-Defect Enhanced Anion Adsorption Energy Toward Super-Rate and Durable Cathode for Ni–Zn Batteries - Yao, Jia; Wan, Houzhao; Chen, Chi; Ji, Jie; Wang, Nengze; Zheng, Zhaohan; Duan, Jinxia; Wang, Xunying; Ma, Guokun; Tao, Li; Wang, Hanbin; Zhang, Jun; et al. (Nano-Micro Letters, 2021)
The alkaline zinc-based batteries with high energy density are becoming a research hotspot. However, the poor cycle stability and low-rate performance limit their wide application. Herein, ultra-thin CoNiO2 nanosheet with rich oxygen defects anchored on the vertically arranged Ni nanotube arrays (Od-CNO@Ni NTs) is used as a positive material for rechargeable alkaline Ni–Zn batteries. As the highly uniform Ni nanotube arrays provide a fast electron/ion transport path and abundant active sites, the Od-CNO@Ni NTs electrode delivers excellent capacity (432.7 mAh g−1) and rate capability (218.3 mAh g−1 at 60 A g−1). Moreover, our Od-CNO@Ni NTs//Zn battery is capable of an ultra-long lifespan (93.0% of initial capacity after 5000 cycles), extremely high energy density of 547.5 Wh kg−1 and power density of 92.9 kW kg−1 (based on the mass of cathode active substance). Meanwhile, the theoretical calculations reveal that the oxygen defects can enhance the interaction between electrode surface and electrolyte ions, contributing to higher capacity. This work opens a reasonable idea for the development of ultra-durable, ultra-fast, and high-energy Ni–Zn battery. Highlights: 1 Ultra-thin CoNiO2 nanosheet with rich oxygen defects anchored on the vertically arranged Ni nanotube arrays (Od-CNO@Ni NTs) is successfully constructed. 2 The Od-CNO@Ni NTs electrode delivers extraordinary electrochemical performance. 3 The theoretical calculations reveal that oxygen defects effectively improve the electrochemical kinetics and the surface electronic state structure of Od-CNO @ Ni NTs, thus exhibiting strong OH − adsorption capacity.